Strengthening the Pharmaceutical System in the Kingdom of Saudi Arabia : Towards a Medicine Policy to Support Vision 2030 - Alghaith, Taghred; Almoteiry, Khalid; Alamri, Adwa; Alluhidan, Mohammed; Alharf, Adel; Al-Hammad, Bander; Aliafali, Ibrahim; Seiter, Andreas; Pisani, Elizabeth; Herbst, Christopher H.; El-Saharty, Sameh; Alazemi, Nahar (World Bank, Washington, DC, 2021)
This document presents the major issues that were discussed in the process of working towards the development of a new medicines policy in Saudi Arabia, examining current national practice in light of international practices and experiences. The document is designed to foster discussion and help inform the development of a new national medicine policy. A detailed accounting of the evidence informing policy choices to be highlighted in an updated medicine policy are presented in Part I of this discussion paper; a proposed new National Medicine Policy itself is presented in Part ll. A new Medicine policy, once finalized and approved, will need to be implemented in a highly dynamic environment and must therefore allow for flexibility. It will need to be followed by the implementation of regulations, closely monitored, and adapted as necessary over time.